Problematic Aspects of Divulging the Secrecy of Adoption - KOSTYUK, MIKHAIL; KUNTS, ELENA (The journal of contemporary issues in business and government, 2021)
Ensuring and protecting the interests of children in a democratic state governed by the rule of law has always been and remains a priority task of any democratic state, insofar as children are the most vulnerable and most unprotected part of modern society, and they should not be deprived of rights. The problem of criminal legal protection of childhood and minors is relevant for all states, including the Russian Federation. The legal system of the Russian Federation in the field of ensuring the rights of children is a set of international and national legal acts that ensure the normal moral and spiritual development of children and minors. In the domestic national legal system, the guarantor of the rights and interests of the child and minors is the Constitution of the Russian Federation, which stipulates that marriage and family, motherhood, fatherhood and childhood are under the protection of the state, and that taking care of children and their upbringing is a natural right and duty of parents. The current situation can be explained by the fact that only deliberate disclosure of the secret of adoption is criminally punishable, the disclosure of this information by negligence does not constitute a crime under Art. 155 of the Criminal Code of the Russian Federation, since the property and other rights of adopted persons are guaranteed by the protection of the Family Code of the Russian Federation. Disclosure of the secret of adoption may not cause significant damage to the property rights of the adopted child. The unformed psyche of a minor, the understanding that there is no consanguinity between close relatives, which until recently were the most native to him, is stress that can lead to suicide. The ways of improving the criminal legal protection of minors from divulging the secrets of adoption are proposed.